2002
DOI: 10.1111/j.1095-8649.2002.tb01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of consistency between the trophic interrelationships of five sparid species in two adjacent central Mediterranean coastal lagoons

Abstract: Both interspecific and intraspecific inter-lagoon differences, between the central Mediterranean coastal lakes of Fogliano and Caprolace, in the trophic patterns of the examined species Diplodus annularis, Diplodus puntazzo, Diplodus sargus, Lithognathus mormyrus and Sparus aurata were revealed by means of correspondence analysis. The most evident inter-lagoon qualitative and quantitative diet changes were observed in S. aurata. Feeding similarities among species were synthesized for each lake by means of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…The data presented indicates that D. sargus is an omnivorous and a generalist species, which is in line with previous studies in the South African marine littoral (Christensen, 1978;Joubert and Hanekom, 1980), in the Medes Islands, Mediterranean coast of Spain (Sala and Ballesteros, 1997), in the Fogliano and Caprolace lakes in Italy (Mariani et al, 2002), in the shallow coastal areas of Faial Island, Azores (Figueiredo et al, 2005), and in the Caprolace coastal lagoon, Italy (Costa and Cataudella, 2007). D. sargus is carnivorous earlier in its life and gradually increases the proportion of algae in its diet; it may ingest algae to collect their epiphyte diatoms (Joubert and Hanekom, 1980), to extract nutrients directly from the algae (Mann and Buxton, 1992) or to optimize the digestion of animals (Lobel, 1981).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data presented indicates that D. sargus is an omnivorous and a generalist species, which is in line with previous studies in the South African marine littoral (Christensen, 1978;Joubert and Hanekom, 1980), in the Medes Islands, Mediterranean coast of Spain (Sala and Ballesteros, 1997), in the Fogliano and Caprolace lakes in Italy (Mariani et al, 2002), in the shallow coastal areas of Faial Island, Azores (Figueiredo et al, 2005), and in the Caprolace coastal lagoon, Italy (Costa and Cataudella, 2007). D. sargus is carnivorous earlier in its life and gradually increases the proportion of algae in its diet; it may ingest algae to collect their epiphyte diatoms (Joubert and Hanekom, 1980), to extract nutrients directly from the algae (Mann and Buxton, 1992) or to optimize the digestion of animals (Lobel, 1981).…”
Section: Discussionsupporting
confidence: 92%
“…obs.). Although the diets of these species are well known in other habitats (Christensen, ; Gon and Ben‐Tuvia, ; Rosecchi, ; Mirto et al., ; Sala and Ballesteros, ; Mariani et al., ; Bartulovic et al., ; Figueiredo et al., ; Sá et al., ; Chrisafi et al., ), there is a lack of knowledge concerning their diets in tidal pools but which is important to know in order to understand why juveniles use these environments in such high numbers in the spring and summer.…”
Section: Introductionmentioning
confidence: 99%
“…Blaber 1974Blaber , 1984Stoner and Livingston 1984;Booth and Buxton 1997;Havelange et al 1997;. Furthermore, the dietary compositions of different populations of a given sparid species sometimes vary markedly Mariani et al 2002;Tancioni et al 2003), which implies that sparids are highly opportunistic feeders. Although the diets of some sparids do not differ markedly with season (Dia et al 2000;Pallaoro et al 2003), Lithognathus mormyrus has been found to become more selective in its feeding in summer (Kallianiotis et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Due to their excellent flesh, many representatives of this family have a high commercial value. The nine species examined have different ecologies (Domanevskaya and Patokina 1984;Mariani et al 2002;Pita et al 2002) 1 : Diplodus puntazzo feeds as a typical grazer on seagrass beds, D. annularis, D. sargus, D. vulgaris and Spondyliosoma cantharus were found to be generalists and remarkably omnivorous, Lithognathus mormyrus behaves as a strict carnivorous soft bottom feeder, Pagellus acarne is a predator hunting macrofauna. Sarpa salpa is strictly herbivorous grazing on aquatic plants, and Sparus aurata is an euryphagous, opportunistic benthic feeder.…”
Section: Introductionmentioning
confidence: 99%